A study of correlation between posterior palatal seal width and soft palatal angulation with palatal contour - Rupal J Shah; Sanjay B Lagdive; Divyeshkumar B Modi; Bhavyata Darji; Vedanshi A Amin; Ghanshyambhai C Patel (Wolters Kluwer Medknow Publications, 2016)
Context: The spatial relationship of posterior palatal seal (PPS) width and vibrating lines varies among individuals. Such variability could be related to contour of the palate. Aims: The study was carried out to evaluate the relationship between PPS width of the patient intra-orally and cephalometric tracing of the same patient. Second part of the study was formulated to determine whether the anterior and posterior vibrating lines can be distinguished as two separate lines by different observers. Materials and Methods: A lateral cephalogram was made to trace the hard and soft palatal contour, and the angle of the palatal contour was measured with the v-ceph program. Correlation analysis was conducted to examine the relationship between the distance from anterior to posterior vibrating lines and the angle of the palatal contour at the junction of the hard and soft palate. Statistical Analysis Used: The data were analyzed using the Karl Pearson Correlation test. Results: Correlation of the angle of the palatal contour to PPS width, showed perfectly positive value; whereas, correlation of angle between anterior nasal spine-posterior nasal spine (ANS-PNS) and PNS-Uvula (U) to PPS width showed partially positive value. Conclusion: The correlation of angle between hard tissue and soft tissue to PPS width, and the angle between ANS-PNS and PNS-U to PPS width, increases with an increase in PPS width.